2014
DOI: 10.3892/ol.2014.2758
|View full text |Cite
|
Sign up to set email alerts
|

Borderline epithelial tumors of the ovary: Experience of 55 patients

Abstract: The objective of the present study was to evaluate the clinicopathological features and the survival time estimates in patients treated for borderline ovarian tumors (BOTs). A retrospective review of all patients treated for BOTs at the University of Bari (Bari, Italy) between 1991 and 2011 was performed. Data were obtained from hospital records and gynecological oncology charts. A total of 55 patients were identified. The median age was 40 years (range, 13–79 years). The majority of the patients (85.5%) exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
(19 reference statements)
3
21
0
Order By: Relevance
“…A conservative, fertility-sparing surgery could be considered for patients who wish to preserve fertility [5, 6]. Preoperative imaging, then, can significantly contribute by accurately identifying borderline ovarian tumors, although Medeiros’s studies and our present study showed the difficulty of conventional MRI in differentiating between borderline and malignant tumors [24].…”
Section: Discussionmentioning
confidence: 80%
“…A conservative, fertility-sparing surgery could be considered for patients who wish to preserve fertility [5, 6]. Preoperative imaging, then, can significantly contribute by accurately identifying borderline ovarian tumors, although Medeiros’s studies and our present study showed the difficulty of conventional MRI in differentiating between borderline and malignant tumors [24].…”
Section: Discussionmentioning
confidence: 80%
“…The incidence of BOTs is 1.8–4.8 cases per 100,000 females per year 5. They typically have an excellent prognosis with an overall 10 year survival rate of 83-91% 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…Borderline serous tumors/atypical proliferative tumor and low-grade serous cancers demonstrate mutations in KRAS or BRAF and few chromosomal abnormalities. High-grade serous carcinomas harbor mutations in TP53 and are chromosomally highly unstable [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%